INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE OF LISTED HEALTH CARE FIRMS IN NIGERIA - Saidu, Hauwa; Ishaku, Ahmed; Sa'ad, Fatima (Kashere Journal of Management Sciences, 2024)
This study is examines the effect of intellectual capital on financial performance of listed healthcare companies in Nigeria. The study used annual reports and accounts of the sampled companies for the period 2009-2022. Human capital efficiency, structural capital efficiency and capital employed efficiency are used as measures of intellectual capital while return on assets is used as a measure of financial performance. The descriptive statistics, correlation and panel data regression technique are used as methods of data analysis using STATA 12 application package. The study found a significant positive effect between structural capital efficiency and capital employed efficiency on the measure of financial performance. However, human capital efficiency has a negative non-significant effect on return on assets. The study concludes that intellectual capital positively affects financial performance. Furthermore, this study recommends that companies in the healthcare industry should maximize the use of intellectual capital to gain competitive advantage on financial performance